The Contribution of the Nurul Jannah Bunder Pademawu Taklim Council in Maintaining Madura's Local Wisdom Values - Akh. Faqih Kurniawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Hence, the researcher is interested in observing Nurul Jannah Majelis Taklim.This research aims describing Madurese local culture form in Nurul Jannah Majelis Taklim; describing Nurul Jannah Majelis Taklim role in keeping the value of Madurese local culture; and describing Nurul Jannah Majelis Taklim troubles in mantaining the value of Madurese local culture. This research uses qualitative approach and descriptive research type. The results of this research for the first focus (Madurese local culture form in Nurul Jannah Majelis Taklim) are politeness culture called as andhap asor; Bhasa Madurese language which has three levels of politeness bhasa kasar, bhasa tengngaan, dan bhasa alos; ta’dzim/ respecting attitude to the teachers by shaking hands, sitting, and walking politely; tabe manner in majelis or onjhangan; and Tengka in escorting the guest. The results of the second focus (Nurul Jannah Majelis Taklim role in keeping the value of Madurese local culture) are as a training facility in leading religious public activities; a place to learn bhasa madhura; a facility to build akhlakul karimah; a facility of the juvenile delinquency prevention; a place for accostumizing politeness (andhap asor); a place to learn tengka in escorting guests and serving dishes to the guest. The results of the third focus (Nurul Jannah Majelis Taklim’s troubles in mantaining the value of Madurese local culture are) are the low interest and enthusiasm of some members; influences of the new trend; feeling embarassed in showing Madurese Identity; and the low effort in following Majelis Taklim activity.